Bioecos: Suatu Media Berbasis Project Based Learning (PjBL) untuk Mengembangkan Kemampuan Berpikir Kreatif - Chimam, Shella Latifah; Aryani, Ima (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Bioecos is a Project Based Learning (PjBL) multimedia aimed at developing students' creative thinking abilities. This research addresses the observed issue of underdeveloped creative Thinking among junior high school students. The study aims to enhance the creative thinking skills of seventh grade students in science education, specifically on the topic of Ecosystems, using Bioecos based on Project Based Learning. The research method employed is qualitative descriptive. The subjects were seventh grade students from Muhammadiyah 5 Junior High School in Surakarta, with a sample size of 51 students from classes VII-C and VII-D. Data collection utilized observation sheets and project assessment sheets designed in alignment with creative thinking indicators: fluency, flexibility, originality, and elaboration. Based on the research findings, the percentage achievements of creative thinking for each indicator were as follows: fluency indicator at 90.0%, flexibility indicator at 83.6%, originality indicator at 80.6%, and elaboration indicator at 77.9%. The results show that 63% of the students achieved a very creative category, totaling 32 students, while 37% achieved a creative category, totaling 19 students. From the conducted research, it can be concluded that the creative thinking abilities of Muhammadiyah 5 Surakarta Junior High School students in the learning process can be enhanced through the implementation of Bioecos based on Project Based Learning (PjBL).